ANALISIS SENTIMEN MASYARAKAT TERHADAP UU CIPTA KERJA PADA MEDIA SOSIAL TWITTER - Nur Sucahyo; Ike Kurniati; Kris Harvit (JRIS : Jurnal Rekayasa Informasi Swadharma, 2022)
This study aims to determine the public's response to the law on job creation which was passed on October 5, 2020. Processed based on public tweets on Twitter social media. The method used is by analyzing public sentiment in the form of positive, neutral, or negative responses on Twitter social media using the Naive Bayes Algorithm. The data was obtained by crawling on Twitter with 160 related keywords in the period April to June 2021 so that tweets related to the law on job creation were obtained. The results of the study obtained information that positive sentiment as much as 22.79%. Negative sentiment 75.77% and neutral sentiment 1.44%. With these results, negative sentiment has the highest total value